Enhanced ohmic heating and chloride adsorption efficiency of conductive seawater cementitious composite: Effect of non-conductive nano-silica. (1st May 2022) - Tian, Weichen; Liu, Yushi; Wang, Wei
Abstract: Nano-silica (NS) as a non-conductive nanofiller was utilized to promote performance improvement of conductive seawater cementitious composite (NS-CSWCC) manufactured by ohmic heating (OH) curing at −20 °C. NS exhibited great advantage on improving the heating efficiency of OH cured sample. The peak temperature and temperature-increase rate of NS-CSWCC samples increased from 52.7 °C and 0.27 °C/min to 73.4 °C and 0.43 °C/min with NS contents varying from 0 to 0.8 wt%. The enhanced mechanism of NS on heating efficiency was thoroughly clarified. The mechanical property results showed that NS-CSWCC sample with 0.8 wt% NS addition endowed the compressive strength of 83.5 MPa, meeting an increase of 36.4% comparing with that of the sample with no NS addition, indicating the advantage of NS addition on improving the mechanical properties. Besides, NS could also lead to higher Cl − binding ratio of OH cured samples. To be specific, the Cl − binding ratio of the sample with 0.8 wt% NS addition met an increase of 35.1% comparing with the sample incorporating no NS. Detailed micro-physicochemical analyses were conducted to reveal the mechanism behind increased Cl − binding efficiency.